2016
DOI: 10.1177/1077801216636240
|View full text |Cite
|
Sign up to set email alerts
|

“Maybe She Was Provoked”

Abstract: The current study is concerned with the different types of gender stereotypes that participants may draw upon when exposed to news stories about intimate partner violence (IPV). We qualitatively analyzed open-ended responses examining four types of gender stereotypes-aggression, emotional, power and control, and acceptability of violence. We offer theoretical implications that extend past research on intimate terrorism and situational couple violence, the gender symmetry debate, and how stereotypes are formed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…Women's aggression is often attributed more externally (Scarduzio et al, 2017), due to their more general reluctance to engage in aggressive behavior (e.g., Archer, 2004), and so judgements about women's aggression often require explanation (e.g. provocation; Author, in press), with more contextual factors taken into account .…”
Section: Sub-theme 2b: Perception Of Men As Abusers Many Men Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's aggression is often attributed more externally (Scarduzio et al, 2017), due to their more general reluctance to engage in aggressive behavior (e.g., Archer, 2004), and so judgements about women's aggression often require explanation (e.g. provocation; Author, in press), with more contextual factors taken into account .…”
Section: Sub-theme 2b: Perception Of Men As Abusers Many Men Commentmentioning
confidence: 99%
“…Women are less aggressive generally (e.g. see Archer, 2004), which could go part way to explaining why men's violence is often attributed internally, and women's externally (Scarduzio et al, 2017). Indeed, because women are expected to be less aggressive due to the nature of socially constructed gender roles (Seelau et al, 2003), judgements about women's aggression often require explanation (e.g.…”
mentioning
confidence: 99%
“…Vogel, Heimerdinger-Edwards, Hammer & Hubbard, 2011), and indeed the importance of maintaining a sense of masculinity has been found in the narrative accounts of male victims of IPV (Hogan, 2016). However, public perceptions of IPV are influenced by normative perceptions of masculinity and femininity; men are seen to deviate from the normative understanding of masculinity when they perpetrate aggression towards a woman, but also when they are victim to it (Scarduzio, Carlyle, Harris & Savage, 2017). These perceptions may go some way to explaining why men struggle to identify as victims which in turn influences help-seeking behavior (Machado et al, 2016).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Studies from the United States (Scarduzio et al, 2016) South Africa (Abrahams et al, 2006) and Nigeria (Kunnuji, 2015) implicate patriarchal structures and ideologies for proviolence attitudes, beliefs, and stereotypes against women. Similar cross-cultural studies (Grandin and Lupri, 1997;Chang, 1999;Yu, 2011;Nguyen et al, 2013) have found differences among countries.…”
Section: Effects Of Country and Gender On Gender-based Violence Beliementioning
confidence: 99%